If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 56 = 2x + -4 Reorder the terms: 56 + 7x = 2x + -4 Reorder the terms: 56 + 7x = -4 + 2x Solving 56 + 7x = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 56 + 7x + -2x = -4 + 2x + -2x Combine like terms: 7x + -2x = 5x 56 + 5x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 56 + 5x = -4 + 0 56 + 5x = -4 Add '-56' to each side of the equation. 56 + -56 + 5x = -4 + -56 Combine like terms: 56 + -56 = 0 0 + 5x = -4 + -56 5x = -4 + -56 Combine like terms: -4 + -56 = -60 5x = -60 Divide each side by '5'. x = -12 Simplifying x = -12
| 3yi=9i | | 0.3x-0.5-2=21 | | z/25=4 | | U^2-4/u^2-2u | | -8x+17=-7 | | y=(1/3i) | | x^2+14+17=-96 | | x^3+18x^2+72=0 | | 4xd^2=9 | | 4v=v+9 | | 400=-16t^2+160t+0 | | log(9-x)-log(6+x)=3 | | (Z/3)-8=-9 | | 201=3.14(r) | | e=23+-6f | | .5n=-12 | | (Z/10)=-8 | | 12x^2(x+1)=0 | | 3=02m-7 | | 1=3.5x | | (5^3)^8/5^13 | | 21=f-23 | | 8k(4k-4)=-5k-32 | | A-19=11 | | (6w^4x^5)-3= | | 3x-15/4x-20 | | -19=11 | | -2y+15=15 | | -96=8z | | Tan^2x=2-tanx | | 7x-4=x-2 | | 7t+7=9t-11 |